Interaction of diet and long ageing period on lipid oxidation and colour stability of lamb meat. (July 2017) - Ponnampalam, Eric N.; Plozza, Tim; Kerr, Matthew G.; Linden, Nick; Mitchell, Meredith; Bekhit, Alaa El-Din A.; Jacobs, Joe L.; Hopkins, David L.
Abstract: Eighty-four crossbred wether and ewe lambs were allocated to four finishing diets. The diets were: Lucerne pasture (n = 24), Annual ryegrass with sub clover pasture (n = 18), Standard commercial feedlot pellets (n = 24) and Annual ryegrass based pasture and commercial feedlot pellets (500 g/day/head) (n = 18). After 8 weeks of feeding the lambs were slaughtered and the m. longissimus (LL) and m. semimembranosus (SM) were vacuum packaged and held chilled for 5 (fresh) or 60 (long aged) days, after which samples of each were displayed for 4 days under simulated retail conditions. Irrespective of muscle type the long aged samples exhibited a rapid reduction in redness (a*-values) and R630/580 nm ratio values such that consumer acceptable thresholds for both traits were quickly exceeded providing limited shelf life. Long ageing also lead to high TBARS levels measured as MDA mg/kg muscle suggestive of a product likely to exhibit rancidity and off flavours from lipid oxidation.